The Role of Social Sciences in the Development of Students' Ideological Immunity - Narkulov Sukhrob Dustmuratovich (Genius Journals, 2023)
In the article, the role of social sciences in increasing the ideological immunity of students and young people in the process of globalization, the need to teach social and humanitarian sciences in higher education institutions is highlighted
Keywords: globalization; idea; ideology; immunity